Analisis Manajemen Perlakuan pada Ternak Kerbau Albino (Kerbau Bule Kyai Slamet) dalam Tradisi Kirab Malam 1 Suro di Keraton Surakarta Hadiningrat: Penelitian - Ayung Adhi Husodo; M. Ali Mauludin; Lilis Nurlina (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to analyze the management and treatment of Albino Buffalo (Kerbau Bule Kyai Slamet) in the Kirab Malam 1 Suro tradition at the Surakarta Palace. Using a qualitative approach with a case study method, data were collected through observation, in-depth interviews, and documentation. The findings indicate that the treatment of the buffalo consists of three main stages: pre-procession (ritual bathing and parade rehearsal), during the procession (escorted by Abdi Dalem and designated officers), and post-procession. These treatments address not only symbolic and cultural aspects but also refer to animal welfare principles, such as freedom from stress, hunger, and discomfort. The management practices reflect an integration of local wisdom with sustainable livestock practices, making this tradition an example of ethical cultural preservation with a strong emphasis on animal welfare.